Physiological implications, cellular responses and lactational performance of Saanen goats under heat stress - Hooper, Henrique Barbosa (2019)
The exposure to heat can adversely affect animal performance and productivity, particularly when associated with pregnancy. The comprehension of the physiological and cellular responses during heat stress assists the decisions to improve the productivity of goats in a tropical environment. In this context, this study evaluated the physiological and cellular responses of Saanen goats in acute and chronic stress conditions. Healthy Saanen goats were randomly assigned to heat stress treatment, short-term, under solar radiation and in the long-term, in climatic chamber. Data were analyzed using the Statistical Analysis System (SAS). The normality was confirmed using the Shapiro-Wilk test. In acute heat stress, solar radiation caused the increase of cortisol release, respiratory rate and reduced T3 and T4 to restore homeothermia. The expression of p53 (pro-apoptotic protein), Bcl-2 (anti-apoptotic protein), HSP60, HSP70 and HSP90 was higher in leukocyte cells for heat stressed goats. In chronic heat stress at the end of gestation, goats significantly mobilized the increase of respiratory rate to lose heat, with cortisol elevation on the 15 days previous to parturition (P < 0.05), which was even greater at day 15 postparturition. At the cellular level, HSP70 was the most expressed during and after heat challenge, with more transcripts at day 15 postparturition for the heat stressed goats. In mammary epithelial cells, there were an increase in apoptosis-related transcripts, p53 and Bax, for the group undergoing heat stress before parturition. The expression of HSP27 was higher before and after parturition for the same group when compared to the animals in thermal neutrality. During lactation, the stressed goats presented lower milk yield. The heat challenge increased the percentage of fat and decreased lactose. The somatic cell count was higher for stressed goats during all lactation. During lactation, the gene expression of prolactin receptor (PRLr) was lower for heat stress goats, which may explain the reduction in milk production at subsequent lactation. In conclusion, our findings suggest that respiratory rate and HSP70 are reliable biomarkers for assessing the thermal comfort and thermotolerance of Saanen goats under acute and chronic heat stress. In addition, chronic thermal stress at final gestation impaired milk production and milk composition from subsequent lactation.